EKSISTENSI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DALAM MENGURANGI TINDAK PELECEHAN SEKSUAL DI KABUPATEN BENGKALIS - Sufni, Novalia; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In principle, child protection is based on the Law of the Republic of Indonesia Number 35 of 2014 concerning amendments to Law Number 23 of 2002 concerning Child Protection which is carried out based on Pancasila and the 1945 Constitution. The principle of protection is regulated based on the best interest of the child. child), where this principle stipulates that in all actions concerning children carried out by the government, society, legislative and judicial bodies, the interests of the child must be the main consideration. Child protection can also be interpreted as all efforts aimed at preventing, rehabilitating and empowering children who have experienced acts of mistreatment in order to ensure their survival and growth and development naturally, both physically, mentally and socially. Child protection is one of the efforts to protect children so that they can carry out their rights and obligations.This research is a sociological or empirical research, so that what is studied initially is secondary data, then it is continued with research on primary data in the field, or in accordance with the realities of life in society.Based on the results of the study, it shows that the existence of the Office of Women's Empowerment and Child Protection in reducing acts of sexual harassment in Bengkalis Regency has so far carried out socialization and development of schools and villages in Bengkalis Regency regarding sexual harassment, prevention of sexual abuse of children, fulfillment of children's rights, prevention of early marriage, making several programs or policies such as stopping school age marriage and stopping sexual abuse of children, conducting campaign activities to the community by cooperating with other stakeholders as partners, providing complaint services and stages of handling. The driving factors for the Bengkalis Regency Women's Empowerment and Child Protection Service in reducing acts of sexual harassment are socialization, complaint services and psychological assistance. While the inhibiting factors for the Bengkalis Regency Women's Empowerment and Child Protection Service in reducing sexual harassment are victims who do not want to report, bad stigma attached to victims, and lack of public awareness. Efforts made by the Bengkalis Regency Women's Empowerment and Child Protection Office in reducing acts of sexual harassment are social approaches, coordination actions, child safety policies, healing processes, and ongoing socialization.Keywords: Existence, Factors, Efforts, Child Protection, Sexual Harassment